Ultrasound-Mediated Drug Diffusion, Uptake, and Cytotoxicity in a Glioblastoma 3D Tumour Sphere Model - Janith Wanigasekara; Julie Rose Mae Mondala; Patrick J. Cullen; Brijesh K. Tiwari; Gemma K. Kinsella; James F. Curtin (Cells, 2025)
A myriad of biological effects can be stimulated by ultrasound (US) for the treatment of cancer. The objective of our research was to investigate the effect of ultrasound alone and in combination with chemotherapeutic drugs such as doxorubicin (DOX) and temozolomide (TMZ) on human glioblastoma (GBM) and the human epidermoid carcinoma cancer 2D and 3D cell cultures. The results indicated that the US 96-probe device could induce tumour sphere cytotoxicity in a dosage- and time-dependent manner, with multiple treatments augmenting this cytotoxic effect. With enhanced cytotoxicity, US decreased tumour sphere growth metabolic activity, disrupted spheroid integrity, and heightened the occurrence of DNA double strand breaks, resulting in damage to tumour spheres and an inability to rebuild tumour spheres after multiple US treatments. The combination of US and TMZ/DOX enhanced the efficiency of treatment for GBM and epidermoid carcinoma by enhancing induced cytotoxicity in 3D tumour spheres compared to 2D monolayer cells and also by increasing the incubation time, which is the most crucial way to differentiate between the effectiveness of drug treatment with and without US. In conclusion, our data demonstrate that US enhances drug diffusion, uptake, and cytotoxicity using 3D spheroid models when compared with 2D cultures. They also demonstrate the significance of 3D cell culture models in drug delivery and discovery research.